2011
DOI: 10.1029/2010jd015099
|View full text |Cite
|
Sign up to set email alerts
|

Integrated evaluation of aerosols from regional brown hazes over northern China in winter: Concentrations, sources, transformation, and mixing states

Abstract: [1] To evaluate the wintertime regional brown haze in northern China, trace gases and aerosols were measured at an urban site between 9 and 20 November 2009. Ion chromatography and transmission electron microscopy (TEM) were used to investigate soluble ions in PM 2.5 and the mixing state of individual particles. The contrasts between clear and hazy days were examined in detail. Concentrations of the primary gases including NO (55.62 ppbv), NO 2 (54.86 ppbv), SO 2 (83.03 ppbv), and CO (2.07 ppmv) on hazy days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 57 publications
12
102
0
1
Order By: Relevance
“…The deteriorated haze pollution was related to the increase in anthropogenic emissions (Qu et al 2015) and the variations in atmospheric circulations (Hui and Xiang, 2015;Li et al, 2016). These haze layers could spread across northern and eastern China and persist over a week during autumn and winter, inducing elevated PM 2.5 concentration exceeding 500 μg m −3 and instantaneous visibility degradation to less than 200 m Li, Zhou et al, 2011). The tremendous aerosol loading arising from frequent haze events exerted a profound impact on the radiation balance and weather in eastern China (Liang and Xia, 2005;Liu et al, 2007;Gao et al, 2015).…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…The deteriorated haze pollution was related to the increase in anthropogenic emissions (Qu et al 2015) and the variations in atmospheric circulations (Hui and Xiang, 2015;Li et al, 2016). These haze layers could spread across northern and eastern China and persist over a week during autumn and winter, inducing elevated PM 2.5 concentration exceeding 500 μg m −3 and instantaneous visibility degradation to less than 200 m Li, Zhou et al, 2011). The tremendous aerosol loading arising from frequent haze events exerted a profound impact on the radiation balance and weather in eastern China (Liang and Xia, 2005;Liu et al, 2007;Gao et al, 2015).…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…7, the SOR ratio presented an upward trend from a non-haze episode to a haze episode: the average value of SOR was 0.05 in non-haze episodes with a highest value of 0.11, whereas the average value of SOR was 0.27 in haze episodes with a highest value of 0.62, which indicated more intense secondary formation of sulfate in haze episodes. Previous studies suggested that the conversion of SO 2 to sulfate during a haze episode in winter was mainly through the aqueous-phase oxidation of SO 2 by the catalytic oxidation of iron and manganese with weak photochemical activity (low O 3 concentration, high NO 2 concentration and low temperature) during the haze period Li et al, 2011;Wang et al, 2012;Zhao et al, 2013). To evaluate the effect of gas-phase oxidation of SO 2 during the haze period, we analyzed the correlations of SOR with O 3 and temperature in haze episodes and found that low correlations existed between SOR and O 3 (r = -0.53, p = 0.01) and SOR and temperature (r = -0.53, p = 0.01).…”
Section: Secondary Formation Of Sulfate In Haze Episodesmentioning
confidence: 99%
“…Sulfate formation in aqueous solution is generated by the uptake of SO 2 onto wet, pre-existing particles or cloud droplets followed by oxidation by O 3 , H 2 O 2, NO 2 or O 2 catalyzed by Fe(III) and Mn(II) (Seinfeld and Pandis, 2006;Wang et al, 2012). Previous studies found that sulfate is produced mainly by heterogeneous reactions by oxidizing SO 2 on wet, pre-existing particles or cloud droplets under high relative humidity (RH) conditions in haze episode in winter Li et al, 2011;Wang et al, 2012;Zhao et al, 2013). Both laboratory experiments and in situ observations suggest that the aqueous oxidation of SO 2 is attributed to catalysis by metals, such as iron and manganese (Turšič et al, 2003;Li et al, 2011;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…haze-fog) have drawn more and more attention [1,2] . Aerosol is a suspension system that composed of small solid ________________________ particles in the air, which is an important source of material to form fog-haze days [3,4] .…”
Section: Introductionmentioning
confidence: 99%